Public Theology and the linguistic turn - Baard, Rachel Sophia (Stellenbosch theological journal, 2022)
In response to Dirkie Smit's inaugural lecture at the University of Stellenbosch, In Diens van die Tale Kanaäns: Oor sistematiese teologie vandag, the question is raised: what is the relationship between language and theology? Traditionally theology subsumed rhetorical language under confessional language, but this shifted in the twentieth century as theologians started to pay more attention to the ways in which even confessional language shapes human experiences and actions and reflects and constitutes power relations. This linguistic turn has implications for public theology, i.e., theology done for the sake of the public good. First, it relates to the question of the role of culture and the reality of pluralism in theology, pointing to the need for careful balance between the emphasis on the church's own historical language, and the need for critical and pluralistic perspectives to engage that language. At the same time, while the linguistic turn rightly points to the relationship between language and violence, care should be taken not to confuse the two and, in the process, ignore concrete concerns.